Transformation of the development model of the building materials industry with consideration to changes in the economic structure during digitalisation of business processes - O. E. Astafyeva (E-Management)
In the process of digitalisation of the economy, economic integration occurs at the micro, meso and macro levels. There is a need to change the model of industrial development with consideration to the ongoing changes in the economic structure. The article proposes the author’s model for development of the building materials industry, reflecting a new approach to the use of resources and formation of resource potential by a set of enterprises. An attempt has been made to present options for increasing production capacity of industrial enterprises based on the developed scale which allows determining the need to reserve production capacity when enterprises conduct activities in a single ecosystem. The article determined the features of the developed model and its advantages for the building materials industry and related industries, the importance of interaction processes in the formation of economic relations and results. The presented results are of an applied nature, reflect the specifics and directions of development of economics of ecosystems in relation to the industrial sector, determine the role of the building materials industry in the structural transformation of the economy and its purpose in the reproduction process. The search for ways of sustainable industrial development is defined on the basis of the presented development model and opportunities created as a result of the emergence of a new version of industry interaction between economic entities. The essence of reproduction processes in the ecosystem is reflected, considering the functional purpose of economic entities and characteristics of reproduction of fixed assets in industry.